The International responsibility of Israeli Occupation for Natural Resources Exploitation in Palestinian Territories - Abu Arra, Mohammad Zaki (Journal of Economic, Administrative and Legal Sciences, 2021)
The Israeli Occupation tends from the first moment of occupying Palestinian lands to seize and loot all the natural wealth and resources depriving the Palestinians of exploitation them and sovereignty on them by its executive, legislative and military policies despite INALIENABLE RIGHT in the rules of international law and the resolutions United Nations that caused severe effects and damages on the Palestinians.After the General Assembly of the United Nations recognition of the state of occupied Palestine on 29/11/2012 and becoming an observer member state which is considered as a very important step to put The State of Palestine in the frame of international law which enables it to join international entities that are under the United Nation system; joining Rome Statute of the International Criminal Court; It opens the way for the prosecution of the Israeli occupation for its multiple crimes such seizing and wasting the Palestinian natural wealth and to demand compensation for the full damage caused to wealth, the loss of profit and income on the Palestinian state; They are the axes that the research aims to shed light on.
Keywords: Palestinian natural resources; violations of the Israeli occupation; legal adjustment; sovereignty over wealth; international law